Evaluation of the dentate gyrus in adult mice exposed to acetaminophen (paracetamol) on postnatal day 10. Issue 1 (12th January 2021) - Philippot, Gaëtan; Hellsten, Sofie V.; Viberg, Henrik; Fredriksson, Robert
Abstract: Acetaminophen (AAP; or paracetamol) is a widely used nonprescription drug with antipyretic and analgesic properties. Alarmingly, there is an increasing body of evidence showing that developmental exposure to AAP is associated with adverse behavioural outcomes later in life. We have previously shown that relevant doses of AAP in 10‐day‐old mice affected memory, learning and locomotor activity in the adult animals. Interestingly, the neurons of the dentate gyrus (DG) have a relatively late time of origin as they are generated during the first two weeks of postnatal life in rodents. Since the generation of these cells, which are important for memory processing, coincides with our AAP exposure, we aim to investigate if the cytoarchitecture of the DG is affected by postnatal day 10 AAP treatment. In addition, we investigate if markers for differentiation and migration in the hippocampus were affected by the same treatment. We did not observe any visual effects in adult DG cytoarchitecture, nor any changes of markers for differentiation/migration in the hippocampus in 24 hr after exposure. Even though a large effect size was estimated on adult DG thickness following AAP exposure, the estimated 95% CIs around the differences of the means reveal no significant effect. Hence, larger sample sizes are warranted to clarify if neonatal AAP exposure affects adult DG thickness in mice. Abstract : A critical window during brain development has previously been identified where clinically relevant doses of paracetamol on postnatal day 10 affected memory and learning later in life in mice. In this study, this exposure in mice did not induce gross morphological abnormalities of the dentate gyrus (DG) in adulthood. However, large effect sizes were noted on DG thickness and area following this exposure and should be confirmed using larger sample sizes.